Studi Perbandingan Media Belajar English Storytelling Berbasis Visual untuk Siswa Kelas 4 - 5 Sekolah Dasar - Kayla Khalda Nur; Dianing Ratri (Journal of Visual Art and Design, 2025)
English storytelling activities are expected to help children in vocabulary development and sentence construction, especially for English as a second language (ESL) learners, while keeping the learning process fun and creative. However, in English storytelling activities in elementary schools, many children are found memorizing the stories through provided text. This results in children telling the stories without catching the English words and understanding the flow of the story they are telling, so the story can sound monotonous. Therefore, this research examined the application of two learning media as alternative aids for learning English storytelling creatively, i.e., conventional media (a picture book) and modified interactive learning media tailored to English learning needs. This research used a comparative method with the same pictures being used in both media and was limited to targeting students in grades 4 and 5 of elementary school. The result showed that while children who learned with the modified interactive media managed to catch more words than those who learned with the conventional picture book, both media were effective for story comprehension and English learning.